Robotic Surgery: A New Era in Gall Bladder Surgery - Jhinuk, Sarkar Kamrun Jahan (Journal of Bangladesh College of Physicians and Surgeons, 2025)
Abstract not available J Bangladesh Coll Phys Surg 2025; 43: 227-238